Pola Komunikasi Komunitas Batik Dayamaka di Desa Gesikharjo Kecamatan Palang, Kabupaten Tuban - Dayanti, Dwi (Journal of Management, Education and Communication, 2024)
This study aims to examine communication patterns and barriers within the Dayamaka batik community in Gesikharjo Village, Palang District, Tuban Regency.  The research method used a qualitative approach with data collection techniques through observation, in-depth interviews, and documentation. The results of the study show that the communication patterns in the Dayamaka batik community use primary communication patterns, vertical and horizontal communication patterns, the use of digital communication media, and communication patterns based on cultural values and local traditions. Meanwhile, the communication barriers that occur in the Dayamaka batik community are differences in the level of understanding and communication skills, limited access to technology and the internet, and social and cultural factors in communication. This study recommends improving communication and digital literacy and strengthening cultural values as efforts to improve communication effectiveness within the Dayamaka batik community.